Chapter Verso un glossario unico per la statistica ufficiale italiana - Brunini, Claudia (Proceedings e report, 2021)
The paper presents Istat activity with the institutional glossary. Methods and implementation of the glossary are described, given the peculiarity of official statistics terminology, which is actually official and binding given the link and interrelations with regulations and international official guidelines. The work of a specific structure called "Metadata harmonization group" set at Istat to meet the requirements of terms producers (surveys experts) and terms users (methodologists, communication and dissemination experts). Space is then given to the terminological procedures adopted to set new terms and validate existing (mostly the results of surveys, sometimes the variables). A proposal aimed at the glossary translation is then presented, as a complementary aspect of the terminological work; a short analysis of the problems related with the institutional translation is given in the last paraghraphs.